The Evaluation of Suitability of Sustainable Food Agricultural Land to Land Use and Regional Spatial Plan of Boyolali Regency (Case Study: Boyolali and Mojosongo District) - Harpudiansyah, Fauzan Iqbal; Apriyanti, Dessy (P4W IPB, 2025)
Land Use Change occurred in many places in Boyolali Regency, including Boyolali and Mojosongo District. Some factors contributed to that thing, like residential and toll road development. There were some instruments to mitigate, such as Boyolali Regional Law Number 17/2016 and Boyolali Regional Law Number 8/2019. Despite being regulated, the enforcement of these regulations has been suboptimal, leading to changes in agricultural land use to non-agricultural purposes in several areas. Monitoring the law is important to see if it goes well or not. This can be utilized Geographic Information Systems (GIS) with overlay method and on-screen digitization of SPOT-6 imagery. Besides that, Remote Sensing analyzed land use trends using multi-temporal SPOT-6 images of 2018 and 2022. This study aims to determine the extent of land use in 2018 and 2022 as well as to determine the suitability of Sustainable Food Agricultural Land to land use and also evaluate the suitability of Sustainable Food Agricultural Land to the Regional Spatial Plan. Results showed that in 2018, the largest land use class was residential areas, covering 2,437.77 hectares, followed by rice fields and moorland, which covered 1,109.06 and 2,205.74 hectares, respectively. By 2022, residential areas had expanded to 2,625.57 hectares, while rice fields and moorland covered 1,130.54 and 2,145.07 hectares, respectively. Based on the overlay method, the suitability analysis revealed that Sustainable Food Agricultural Land matched 90.47% of land use in 2018 and 90.04% in 2022. Meanwhile, the suitability between the Sustainable Food Agriculture Land and Regional Spatial Plan amounted to 81.03%.